2018
DOI: 10.5194/essd-2018-39
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A rescued dataset of sub-daily meteorological observations for Europe and the southern Mediterranean region, 1877–2012

Abstract: Abstract. Sub-daily meteorological observations are needed for input to and assessment of high-resolution reanalysis products to improve understanding of weather and climate variability. While there are millions such weather observations that have been collected by various organizations, many are yet to be transcribed into a useable format. Under the auspices of the European Union funded Uncertainties in Ensembles of Regional ReAnalysis (UERRA) project, we describe the compilation and development of a digital … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 93 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…These findings are consistent with Min et al (2011) who showed that the signal of changes in extreme rainfall was detectable and attributable to human activity over large parts of the northern hemisphere land areas and with Fischer et al (2014) who used climate model simulations to suggest that emergence of changes in extreme rainfall can occur earlier than changes in mean rainfall. Continued recovery of millions of undigitized weather observations, including for daily rainfall, will improve and lengthen these gridded data sets (e.g., Ashcroft et al, 2018; Hawkins et al, 2019).…”
Section: Emergence Of Unusual Precipitation Amountsmentioning
confidence: 99%
“…These findings are consistent with Min et al (2011) who showed that the signal of changes in extreme rainfall was detectable and attributable to human activity over large parts of the northern hemisphere land areas and with Fischer et al (2014) who used climate model simulations to suggest that emergence of changes in extreme rainfall can occur earlier than changes in mean rainfall. Continued recovery of millions of undigitized weather observations, including for daily rainfall, will improve and lengthen these gridded data sets (e.g., Ashcroft et al, 2018; Hawkins et al, 2019).…”
Section: Emergence Of Unusual Precipitation Amountsmentioning
confidence: 99%
“…Due to the small size and limited financial support for the project, each year of data was only digitized once; that is, the data were not double‐keyed to assist in quality assessment (e.g. Ashcroft et al ., ). However, as we show below, we found very few errors in the digitized data.…”
Section: Description Of the Datasetmentioning
confidence: 97%
“…Twenty‐five local and international volunteers were eventually chosen to enter the daily data, with five of the volunteers entering three or more years. Each volunteer was given a formatted spreadsheet to complete (similar to Ashcroft et al ., and Vagge et al ., ), a list of instructions, and access to a raw data book through the University of Newcastle file sharing system.…”
Section: Description Of the Datasetmentioning
confidence: 99%
“…Although very long and important terrestrial surface and upper air data series have been digitized and processed (e.g. Alcoforado et al ., for Portugal; Camuffo and Bertolin, , Camuffo et al ., and Camuffo et al ., for Italy and the Western Mediterranean; Domínguez‐Castro et al ., for Spain; Brunet et al ., and Ashcroft et al ., for the Mediterranean North Africa and the Middle East; Slonosky, for Canada; Ashcroft et al ., for southeastern Australia; Stickler et al ., for global upper‐air data, to give only very few examples), a huge fraction have still not been digitized (see also Bosilovich et al ., ). This also applies to historical marine observations from exploration, naval, postal, merchant and passenger ships.…”
Section: Climate Data Rescuementioning
confidence: 99%
“…Reanalyses also benefit from upper‐air data (Stickler et al ., ), which is also instrumental in understanding climate change (e.g. Seidel et al ., ; Thorne et al ., ) and from sub‐daily observations (Ashcroft et al ., ). In the polar regions, observations involving ice surfaces and extents are of great importance (e.g.…”
Section: Climate Data Rescuementioning
confidence: 99%